2015
DOI: 10.1590/bjpt-rbf.2014.0114
|View full text |Cite
|
Sign up to set email alerts
|

Skinfold thickness affects the isometric knee extension torque evoked by Neuromuscular Electrical Stimulation

Abstract: BACKGROUND: Subcutaneous adipose tissue may influence the transmission of electrical stimuli through to the skin, thus affecting both evoked torque and comfort perception associated with neuromuscular electrical stimulation (NMES). This could seriously affect the effectiveness of NMES for either rehabilitation or sports purposes. OBJECTIVE: To investigate the effects of skinfold thickness (SFT) on maximal NMES current intensity, NMES-evoked torque, and NMES-induced discomfort. METHOD: First, we compared NMES c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…A design allowing for withinparticipant comparisons was selected in an effort to eliminate the possibility of interparticipant differences resulting in confounding factors. For example, subcutaneous tissue thickness differences 156,161 and personality factors 25 have been shown to impact neuromuscular electrical stimulation (NMES) related outcomes similar to those included in this project. This project was subdivided in the form of two separate manuscripts (Chapter IV and Chapter V).…”
Section: Chapter III -Methodology Study Designmentioning
confidence: 99%
See 4 more Smart Citations
“…A design allowing for withinparticipant comparisons was selected in an effort to eliminate the possibility of interparticipant differences resulting in confounding factors. For example, subcutaneous tissue thickness differences 156,161 and personality factors 25 have been shown to impact neuromuscular electrical stimulation (NMES) related outcomes similar to those included in this project. This project was subdivided in the form of two separate manuscripts (Chapter IV and Chapter V).…”
Section: Chapter III -Methodology Study Designmentioning
confidence: 99%
“…Medeiros et al 161 stimulated the quadriceps in a cohort of healthy women while using a maximum tolerable stimulus intensity, and the women were separated into two groups representing thick and thin subcutaneous tissue amounts. As with Miller et al 156 they observed that greater stimulus intensities were tolerated by those with greater amounts of subcutaneous tissue.…”
Section: Additional Comfort Strategiesmentioning
confidence: 99%
See 3 more Smart Citations